Elemental Composition of Local Pakistani Building Materials Using Instrumental Neutron Activation Analysis (INAA) - Yaqub, A.; Kashif, M.; Siddique, N. (The Nucleus, 2020)
In the present study, elemental composition of local Pakistani building materials (marble, granite, stones and pottery) were determined using Instrumental Neutron Activation Analysis (INAA) technique. On the average, maximum numbers of elements were quantified in marble samples followed by stone and pottery samples. The elemental data was subjected to principal component analysis (PCA) which showed that all marble samples have similar composition. Similarly stones also share the same chemical content and the pottery samples resemble each other. Therefore PCA can be successfully used to differentiate different types of building material samples from their elemental data.